Genome-wide identification of the bHLH gene family in Scutellaria baicalensis and their relationship with baicalin biosynthesis under drought stress - Sun, Yingxin; Wang, Beier; Zhang, Lichao; Zheng, Xiaohan; Xu, Peng; Zhang, Meng; Han, Meiguang; Di, Peng; Han, Mei; Cheng, Lin; Yang, Limin (Frontiers in Plant Science, 2025)
The bHLH gene family plays a critical role in regulating internal responses in plants. Although the pharmacological properties of Scutellaria baicalensis have been extensively studied, its bHLH gene family remains poorly investigated. In this study, 142 SbbHLH genes were identified using the complete genome data of S. baicalensis. Phylogenetic and conserved motif analyses were performed. Gene duplication events were analyzed, and cis-element analysis was conducted to explore regulatory factors. The expression patterns of these genes in different tissues and under drought stress were investigated using transcriptome data and qRT-PCR analysis. Phylogenetic and conserved motif analyses revealed that the gene structures within each SbbHLH clade are relatively conserved. Gene duplication analysis identified 29 duplication events in the SbbHLH gene family, most of which involved gene pairs under purifying selection. Cis-element analysis revealed that these genes are regulated by various environmental and hormonal factors. Transcriptomic data and qRT-PCR results demonstrated tissue-specific expression patterns for the 142 SbbHLH genes. Additionally, bHLH genes potentially involved in baicalin biosynthesis were identified under drought stress. The findings suggest that under drought stress, SbbHLH74, SbbHLH98, and SbbHLH142 are regulated by a network centered on SbbHLH53, which enhances baicalin biosynthesis. In conclusion, this study provides a comprehensive analysis of the bHLH gene family in S. baicalensis and identifies 4 potential SbbHLH genes involved in regulating baicalin biosynthesis under drought stress.